Meeting Physical Activity and Screen Time Among Colombian Adolescents with or Without Sensory-Related Problems - Garcia-Hermoso, A (John Wiley and Sons Inc, 2021)
The aim of this study was to assess the extent to which adolescents with and without visual and hearing-related problems meet physical activity (PA) and recreational screen time (ST) recommendations in a representative Colombian sample. A total of 35,404 adolescents aged 13–17 years were included from the Encuesta Nacional de Salud Escolar (ENSE) (Colombia). Sociodemographic-related information, anthropometric variables, PA, ST, and both visual- and hearing-related problems were collected by self-administered questionnaires. The prevalence of adolescents meeting with PA, ST, and both recommendations was 14.8%, 53.4%, and 7.8%, respectively. Both sexes with visual- (males: OR=0.70, 95%CI 0.59–0.83; females: OR=0.73, 95%CI 0.61–0.88) and hearing-related problems (males, OR=0.75, 95%CI 0.61–0.93; females, OR=0.76, 95%CI 0.61–0.94) are less likely to meet combined recommendations. Sensory problems such as vision- and hearing-related problems could be considered key barriers to engagement in PA and facilitators of recreational ST in Colombian adolescents. © 2021 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd